Tobacco Use and Its Effects on the Pulp and Periapical Tissues: An Integrative Review and Thematic Analysis - , Luiz Carlos Trevia Morais Correia Viana; , José Evando da Silva-Filho; , Larissa Pinheiro Barreto; , Bernardo de Almeida Aguiar; , Fábio de Almeida-Gomes; , Christina César Praça-Brasil (Archives of Current Research International, 2025)
Aims: To conduct an integrative literature review investigating the association between tobacco use and pulpal and periapical alterations, rather than general periodontal disease. Methodology: A literature search was performed in PubMed and Google Scholar for studies published between 2018 and 2024. Twenty-one studies met the inclusion criteria and were analyzed using an integrative review approach and thematic analysis. Four main themes were identified: (1) increased susceptibility to pulpal and periapical inflammatory diseases; (2) impaired healing and treatment outcomes; (3) contradictory findings on smoking and periapical lesions; and (4) methodological heterogeneity across studies. Results: The majority of studies (80%) reported that smokers are more likely to develop pulpal necrosis and periapical lesions, experience delayed healing, and have poorer clinical outcomes in endodontic treatments. Tobacco use was associated with elevated inflammatory responses, larger lesion size, impaired tissue repair, and less predictable endodontic healing. Animal models demonstrated exacerbated pulpal and periapical inflammation with nicotine exposure, particularly when combined with alcohol. However, some studies (20%) reported no significant association, highlighting variability due to differences in diagnostic criteria, population characteristics, and follow-up periods. Conclusion: Smoking is a critical risk factor for pulpal and periapical pathologies, negatively affecting tissue repair and treatment success. Integrating smoking cessation strategies into oral health programs is essential to mitigate both local and systemic effects of tobacco use and improve clinical outcomes.